Effect of dietary digestible energy content on expression of genes of lipid metabolism and LC-PUFA biosynthesis in liver of Atlantic salmon (Salmo salar L.) - Martinez-Rubio, Laura; Wadsworth, Simon; Vecino, Jose L G; Bell, J Gordon; Tocher, Douglas R (Aquaculture, 2013)
The relationship between lipid and digestible energy content of the feed and growth performance has been exploited with great effect in Atlantic salmon (Salmo salar). The precise metabolic consequences of so-called "high-energy" feeds have not been fully defined, but increased and altered tissue lipid deposition patterns impacting on carcass and product quality have been reported. Recent studies on global gene expression have shown that dietary lipid and digestible energy content can have significant effects on gene expression in salmonids. In addition, we recently showed that functional feeds with reduced digestible energy significantly improved outcomes in response to inflammatory disease in salmon. The present study aimed to elucidate and clarify the effects of dietary digestible energy content (22, 20 and 18 MJ/kg; HE, ME and LE diets, respectively) on lipid and fatty acid metabolism in salmon fed diets containing graded amounts of lipid. Specifically the effects on liver lipid and fatty acid compositions, and on the hepatic expression of genes of lipid and fatty acid metabolism were determined. Final weight and weight gain were significantly higher, and FCR lower, in fish fed the HE diet. Crude lipid content was significantly lower in fish fed the LE diet compared to fish fed the two higher energy contents. Significantly lower total lipid and triacylglycerol levels were recorded in liver of fish fed the LE diet compared to fish fed the higher energy diets. Liver lipids in salmon fed the LE diet had generally significantly higher proportions of saturated fatty acids and long-chain polyunsaturated fatty acids (LC-PUFA), and lower monounsaturated fatty acids, C18 and n - 6 PUFA. Consistent with this, salmon fed the LE diet showed increased liver expression of both Δ6 and Δ5 fatty acyl desaturases in comparison to fish fed the diets with higher energy levels. Fatty acid synthase expression showed a clear upward trend as dietary energy decreased, and sterol regulatory element binding protein 2 and liver X ...